Assessing the Impact of Work Environment on Worker Performance at Federal Polytechnic Ekowe, Bayelsa State - Igarando, Alalawari Anne; Teilanyo, Edith Chioma; Oladunjoye, Patrick (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Organizations must explore innovative work practices and cultivate a positive environment where employees feel valued and motivated. This study examined the impact of the work environment on employee performance at Federal Polytechnic Ekowe. A survey was conducted with 400 staff members, encompassing both senior and junior employees, through the use of questionnaires. The findings indicated that the work environment significantly influences employee performance, and addressing identified issues could enhance productivity. Key challenges include feedback on employee performance, job support, and the physical work environment. The study recommends that the organization organize regular meetings for employees to voice management concerns, fostering motivation. Furthermore, management should focus on creating an environment that attracts, retains, and motivates employees, promoting a comfortable workplace and boosting overall organizational productivity.